Konsep Perencanaan Infrastruktur Minapolitan di Kecamatan Mattiro Sompe Kabupaten Pinrang - Fitrawan Umar; Shirly Wunas; Yashinta Kumala Dewi Sutopo (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
Minapolitan is the concept of marine based on economic development region. Development of the Minapolitan area should be supported by adequate infrastructure. As the area is planned to be Minapolitan, the district of Mattiro Sompe, Pinrang regency, requires infrastructure planning in order to encourage fishing activities which develop in the area. This study aims to identify the availability and the needs of Minapolitan infrastructure, as well as the planning concept of Minapolitan infrastructure in Mattiro Sompe district, Pinrang. The study was conducted using qualitative and quantitative methods resulting the description about the availability of Minapolitan infrastructure as well as estimated Minapolitan infrastructure for the future. The study resulted the planning concept of Minapolitan infrastructure to increase the fisheries production and develop regional economic, as well as the zoning concept to distribute the facilities in Mattiro Sompe district.